Beneficial effects of exercise training on cognitive performances during total sleep deprivation in healthy subjects - Sauvet, Fabien; Arnal, Pierrick J.; Tardo-Dino, Pierre-Emmanuel; Drogou, Catherine; Van Beers, Pascal; Erblang, Mégane; Guillard, Mathias; Rabat, Arnaud; Malgoyre, Alexandra; Bourrilhon, Cyprien; Léger, Damien; Gomez-Mérino, Danielle; et al. (Sleep medicine, 2020)
Exercise training has been shown to improve learning and memory, and to protect against the negative impact of sleep deprivation. The aim of this study was to investigate the effects of seven weeks of moderate- and high-intensity interval exercise training on vigilance/sustained attention, inhibition processes and working memory during 40-h total sleep deprivation (TSD) in 16 healthy young men. The subjects were evaluated before (Baseline, BAS) and during TSD, and the day after a night of recovery sleep (Recovery, REC). Exercise training significantly decreased errors and increased speed assessed by the psychomotor vigilance task (PVT) during TSD and REC while no difference was found in executive inhibition (Go–noGo task) and working memory (2-Back task) performances. The multiple sleep latency test results were higher during BAS and REC at Post-exercise training, and no difference occurred in subjective sleepiness and daytime microsleeps over the 40-h TSD. The PVT speed was positively correlated with maximal oxygen consumption and maximal aerobic power measured before entry in the in-laboratory TSD protocol, and stage 3 sleep duration measured during the first night in the in-laboratory TSD protocol (N-1). Exercise training effects on sleep were found during the night recovery with lower stage-3 sleep and higher rapid eye movement (REM) sleep durations. An exercise training effect was also found on free insulin-like growth factor I levels with lower levels during TSD at Post-exercise training. In healthy young men, exercise training reduced sleep pressure at baseline and protected against sustained attention deficits induced by TSD with persistent effect after one night of recovery sleep. Nevertheless, exercise training was not effective in reducing deficits in executive inhibition and working memory induced by TSD. •Sleep deprivation triggers deficits on vigilance/sustained attention, executive processes and working memory.•Exercise training limits sustained attention deficits induced by total sleep deprivation.•Exercise training could be considered as a relevant countermeasure to sleep debt.•Beneficial effects of exercise training on vigilance/sustained attention may be associated with higher aerobic fitness and/or Slow Wave Sleep.